Keragaan Kelembagaan Pasar Lelang dalam Pemasaran Produk Pertanian - Syam, Lia Fauziah; Suharno, Suharno; Kusnadi, Nunung (Jurnal Agribisnis Indonesia, 2023)
Auction is one of the pricing mechanisms that has been widely applied in various fields. The auction market which was widely applied to non-agricultural goods has now developed in agriculture such as the chili auction market in Panjatan District, Kulon Progo Regency. The purpose of this study is to describe the institutional profile of the chili auction and the process of implementing the chili auction managed by farmers in Panjatan District, Kulon Progo Regency. Descriptive analysis used to analyze the institutional profile of the chili auction market and the auction process. The results showed that the institutional auction market in the District of Panjatan is an institution that is managed jointly by chili farmers in the District of Panjatan with the terms that have been mutually agreed upon. The auction mechanism is carried out in three stages, namely pre-auction activities, auction activities and post-auction activities. Determination of auction prices using the mechanism of the first price auction. This auction mechanism will minimize collusion between traders, and force traders to compete for chili supply from farmers in Panjatan District with the highest price offer that can be given.